2011
DOI: 10.1590/s0004-27302011000800019
|View full text |Cite
|
Sign up to set email alerts
|

Weight-adjusted neonatal 17OH-progesterone cutoff levels improve the efficiency of newborn screening for congenital adrenal hyperplasia

Abstract: Weight-adjusted neonatal 17OH-progesterone cutoff levels improve the efficiency of newborn screening for congenital adrenal hyperplasia ABSTRACTObjective: To evaluate weight-adjusted strategy for levels of neonatal-17OHP in order to improve newborn screening (NBS) efficiency. Subjects and methods: Blood samples collected between 2-7 days of age from 67,640 newborns were evaluated. When N17OHP levels were ≥ 20 ng/mL, and a second sample was requested. We retrospectively analyzed neonatal-17OHP levels measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
6
30
0
3
Order By: Relevance
“…The classical form frequency is approximately 1:10 000 to 1:15 000 live births, whereas the NC form is much more frequent and is estimated to have a frequency of 1 in 100-1000 in the general population (2,3,4,5). The 21-hydroxylase coding gene (CYP21A2) and its pseudogene (CYP21A1P) extend over a long region in the short arm of chromosome 6, alternating in tandem with C4A and C4B genes.…”
Section: Introductionmentioning
confidence: 99%
“…The classical form frequency is approximately 1:10 000 to 1:15 000 live births, whereas the NC form is much more frequent and is estimated to have a frequency of 1 in 100-1000 in the general population (2,3,4,5). The 21-hydroxylase coding gene (CYP21A2) and its pseudogene (CYP21A1P) extend over a long region in the short arm of chromosome 6, alternating in tandem with C4A and C4B genes.…”
Section: Introductionmentioning
confidence: 99%
“…Premature children and those with low weight have higher risk of false positive results in the neonatal screening test analyzed by the fluoroimmunoassay, method, which is the international standard (5,28). Adoption of more precise cutoff levels for 17OHP, according to gestational age and birth weight, decrease the rate of false positivity and identify individuals at risk of adrenal crisis from those with mild forms of the disease (28,29). Newborns with false-positive results have elevated levels of 17OHP, but are asymptomatic.…”
mentioning
confidence: 99%
“…Allen et al observed that there is a tenfold increase in positive predictive value of screening results when 17-OHP levels were categorized according to birth weight 16 . To reduce false positive levels, Barra et al 17 and Hayashi et al, 7 used weight adjusted criteria in the newborn screening programs. In this study, decision values are fixed based on birth weights.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous study, 75% of infants with classical CAH have the severe salt-wasting (SW) form of the disease with electrolyte abnormality and shock which leads to death. 7 Delayed diagnosis of babies with salt-wasting CAH still remains a major clinical problem. Affected infants should be followed up until there is a correct diagnosis or normalization of serum 17-OHP levels.…”
Section: Introductionmentioning
confidence: 99%